2014
DOI: 10.1177/1479164114533357
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between blood pressure and sciatic nerve blood flow velocity in rats with insulin-treated experimental diabetes

Abstract: Peripheral nerve blood flow (NBF) does not autoregulate but, instead, responds passively to changes in mean arterial pressure (MAP). How this relationship is impacted by insulin-treated experimental diabetes (ITED) is unknown. We tested the hypothesis that ITED will reduce NBF across a range of MAP in Sprague Dawley rats. Following 10 weeks of control or ITED conditions, conscious MAP (tail-cuff) was measured, and under anaesthesia, the MAP (carotid artery catheter, pressure transducer) and NBF (Doppler ultras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
(128 reference statements)
0
2
0
Order By: Relevance
“…A light plane anesthesia 0.5–1.2 g/kg has been shown to maintain the integrity of the cardiovascular system, where higher doses of urethane (above 1.5 g/kg) can produce hypotension and bradycardia, as well as high rates of mortality [ 91 , 92 ]. In the current study we used a minimal dose of 25 mg/kg, which was reported in previous studies by our laboratory to have little influence on neurovascular blood flow measures [ 93 95 ]. That being said, it cannot be determined to what extent, if at all, the autonomic nervous system was augmented by the urethane-chloralose treatment in comparison to conscious animals.…”
Section: Discussionmentioning
confidence: 99%
“…A light plane anesthesia 0.5–1.2 g/kg has been shown to maintain the integrity of the cardiovascular system, where higher doses of urethane (above 1.5 g/kg) can produce hypotension and bradycardia, as well as high rates of mortality [ 91 , 92 ]. In the current study we used a minimal dose of 25 mg/kg, which was reported in previous studies by our laboratory to have little influence on neurovascular blood flow measures [ 93 95 ]. That being said, it cannot be determined to what extent, if at all, the autonomic nervous system was augmented by the urethane-chloralose treatment in comparison to conscious animals.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the hemodynamic response to insulin is impaired in T2D . This impaired hemodynamic response to insulin has been observed in numerous tissues, including intestine, brain, nerve, and muscle, but, to our knowledge, has not been investigated in bone. In the vascular endothelium, insulin activation of the pI3/Akt pathway promotes vasodilation mediated by endothelial‐nitric oxide synthase (eNOS) and reduces synthesis of deleterious adhesion molecules (eg, vascular cell adhesion molecule 1 [VCAM‐1]).…”
Section: Introductionmentioning
confidence: 90%